THE EFFECT OF COMPENSATION ON EMPLOYEES PERFORMANCE OF IMPERIAL CLUB GOLF TANGERANG DISTRICT - Sutoro, Moh. (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
Compensation problems have become talks between employees, and the impact of motivation and employee performance decreases. To answer this problem, analysis and research are needed, so that a solution is found. This study uses a quantitative approach with multiple linear regression analysis. The total number of employees is 50 people, so the technical sample used is the census. Furthermore, the research was carried out by testing the stages of analysis which included descriptive analysis of the questionnaire, validity test, reliability test, classic assumption test, linear regression test, correlation coefficient test and test coefficient of determination. The results of the regression analysis show that the compensation has a positive and significant effect on the performance of Imperial Club Golf employees with a regression coefficient of 0,618 and Tcount of 7,156.